A Comprehensive Survey of Brain–Computer Interface (BCI): Definitions, Applications, Techniques, Challenges, and Future Work - Ali, Sawsan Ali Babiker; Ahmed, Yousif Elhadi Elsideeg; Amien, Magdi B.M.; Musa, Suhaila M.A. (Gezira Journal of Engineering and Applied Sciences; Vol 19 No 2 (2024), 2026)
Brain-computer interfacing is one of the significant outcomes of rapid developments in information and communication technology along with the advances of bio-sciences. Sensing and data acquisition technologies have provided the capability of capturing the brain bio-signals that represents the brain status and behavior. Further, efficient signal processing and features extraction methods have been developed and implemented considering the contribution of computation for more accurate findings. Therefore, the applicability of brain-computer interfacing based systems has become more attractive for future trends. Among this very rich and complex context, an intensive investigation and exploration could be helpful for researchers interested in this area. This paper aimed to sum up a milestone of the great contributions and outcomes in the brain-computer interfacing scope for researchers and promote several promising indicators for future efforts. It provides a well underlying background, explores the most advanced data acquisition technologies, and investigates and estimates recent contributions to signal processing. The paper also features extraction methods and classifiers, and highlights the significance of the applications considering the most common challenges such as anatomical and bio-signal characteristics, performance, efficiency, accuracy and ethics. Then, it proposes some further promising concepts, methods and ideas to be investigated, and innovative objectives to be achieved. تعد واجهات الدماغ والحاسوب إحدى النتائج الهامة للتطورات السريعة في تكنولوجيا المعلومات والاتصالات جنبا إلى جنب مع التقدم في العلوم الحيوية. لقد وفرت تقنيات الاستشعار واكتساب البيانات القدرة على التقاط الإشارات الحيوية الدماغية التي تمثل حالة الدماغ وسلوكه. علاوة على ذلك، تم تطوير وتطبيق طرق فعالة لمعالجة الإشارات   واستخلاص المميزات، مع الأخذ في الاعتبار مساهمة الحوسبة من أجل التوصل إلى نتائج أكثر دقة. وبالتالي، أصبحت قابلية تطبيق الأنظمة القائمة على واجهات الدماغ والحاسوب أكثر جاذبية للتوجهات المستقبلية. ضمن هذا السياق الغني والمعقد، يمكن أن يكون إجراء تحقيق واستكشاف مكثف مفيدا للباحثين المهتمين بهذا المجال. تهدف  هذه الورقة إلى تلخيص للإسهامات والنتائج العظيمة في نطاق واجهات الدماغ والحاسوب للباحثيين، وتعزيز العديد من المؤشرات الواعدة للجهود المستقبلية. إنها توفر خلفية تأسيسية جيدة؛ وتستكشف أكثر تقنيات اكتساب البيانات تقدما؛ وتبحث وتقيم الإسهامات الحديثة في معالجة الإشارات، وطرق استخلاص المميزات، والمصنفات؛ وتسلط الضوء على أهمية التطبيقات مع مراعاة التحديات الأكثر شيوعا مثل الخصائص التشريحية والخاضة بلإشارات الحيوية، والأداء، والكفاءة، والدقة، والأخلاقيات. ثم تقترح بعض المفاهيم، والطرق والأفكار الواعدة الإضافية للبحث، والأهداف المستحدثة الواجب تحقيقها.